ROOTS OF KASHMIR STRIFE AND THE SAGA OF GILGIT BALTISTAN (GB) - Haji Muhammad Anwar; Dr. Abdul Qadir Mushtaq; Muhammad Hasnain (`, 2024)
Kashmir debacle is a faulty demarcation of the partition plan between India and Pakistan. The conflict of Kashmir was not only a political dispute between India and Pakistan but an ethnic, religious and territorial dispute as well. In this conflict, the perceptions of Pakistan and India about the GB are entirely different. Pakistan assimilated the GB with Kashmir strife and considered it an unfair partition of the British rulers who ignored the self-determination right of the local masses. Quite to the contrary, India regarded it as a territorial issue and said that Jammu and Kashmir including the GB is a vital part of India. The Indian territory has occupied illegally by Pakistan. But the aspiration of the masses of the GB and historical background are vice versa. In this paper, an effort has been made to disclose the point that how the GB became the part of Kashmir discard in accordance with the proposition of India and Pakistan and what are the historical facts of the GB which remained oblivion in the political debates? The crux of the paper is that the GB is quite extraordinary case and has stuck in the whirl of Kashmir discard due to the strategic lapses of indigenous policies. It is such a region in the country of Pakistan that emancipated its region by fighting of its own and vanquished their enemies and by their freewill acceded to Pakistan. But the region has not become a full-fledged constitutional part of Pakistan yet and waiting for a pragmatic resolution to this longstanding issue between Pakistan and India. Key Words: Kashmir Strife, Gilgit Baltistan, India’s view about the GB, Pakistan’s narrative about the GB